Dental students' perceptions on the contribution and impact role of a clinical teacher - Shoaib, L.A.; Safii, S.H.; Naimie, Z.; Ahmad, N.A.; Sukumaran, P.; Yunus, R.M. (Blackwell Publishing, 2018)
Objectives: This study was conducted in University of Malaya to evaluate student perceptions on the contribution and role of an effective clinical teacher based on the cognitive apprenticeship model in clinical practice. Methods: Self-administered questionnaires were distributed to 233 undergraduate dental students involved with clinical teaching. This modified and validated questionnaire focusing on students' learning environment was used in order to gain relevant information related to dental clinical teaching. Six domains with different criteria applicable to clinical teaching in dentistry were selected consisting of modelling (four criteria), coaching (four criteria), scaffolding (four criteria), articulation (four criteria), reflection (two criteria) and general learning environment (six criteria). Data analyses were performed using IBM SPSS Statistics 20. Results: Majority of the students expressed positive perceptions on their clinical learning experience towards the clinical teachers in the Faculty of Dentistry, University of Malaya, in all criteria of the domains. Few negative feedbacks concerning the general learning environment were reported. Conclusion :Further improvement in the delivery of clinical teaching preferably by using wide variety of teaching-learning activities can be taken into account through students' feedback on their learning experience.